2017
DOI: 10.1007/s11136-017-1620-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effect of peer helping in a coping skills intervention: a randomized controlled trial for advanced gastrointestinal cancer patients and their family caregivers

Abstract: Although a telephone-based intervention is feasible and acceptable for this population, peer helping in the context of a coping skills intervention does not enhance spiritual well-being relative to coping skills alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(86 citation statements)
references
References 54 publications
(60 reference statements)
0
82
0
Order By: Relevance
“…All these studies reported interventions driven by a framework that targeted change of thoughts and/or behaviour through CBT techniques such as psycho‐education, goal setting, problem solving, cognitive reappraisal, relaxation/mindfulness training, coping skills training, stress management, and activity planning/pacing. The targets of these interventions were varied and included quality of life, distress (depression and anxiety), and disease‐specific symptoms …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies reported interventions driven by a framework that targeted change of thoughts and/or behaviour through CBT techniques such as psycho‐education, goal setting, problem solving, cognitive reappraisal, relaxation/mindfulness training, coping skills training, stress management, and activity planning/pacing. The targets of these interventions were varied and included quality of life, distress (depression and anxiety), and disease‐specific symptoms …”
Section: Resultsmentioning
confidence: 99%
“…We classified 20 studies as CBT based. All these studies reported interventions were varied and included quality of life, [11][12][13][14][15][16][17] distress (depression and anxiety), [18][19][20][21][22][23][24] and disease-specific symptoms. 25…”
Section: Cbt-based Interventionsmentioning
confidence: 99%
“…Moreover, caregivers’ influence on patients’ outcomes has been gradually explored (Kootker et al, 2019; McCarthy, Bakas, Schellinger, Stapleton, & Kissela, 2019). Lastly, inventions for caregivers or patient–caregiver dyads have been attempted in recent years (Marcotte, Tremblay, Turcotte, & Michaud, 2019; Mosher et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The trial design and methods have been published previously [30]. Following Indiana University institutional review board approval, potentially eligible patients were identified via chart review and consultation with the attending oncologist and were approached by a research assistant during an oncology clinic visit.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, both patients and caregivers had to be ≥18 years of age and fluent in English. Given our interest in intervening with participants with clinical and subclinical levels of distress [30], one or both dyad members had to report a score of 3 or higher on the 0-10 Distress Thermometer scale [31].…”
Section: Participantsmentioning
confidence: 99%